Using the explicit method to solve parabolic partial differential equations of temperature distribution in the conductor of a crude circuit breaker - Saratha Sathasivam; Shehab Abdulhabib Alzaeemi; Muraly Velavan; Mustafa Mamat; Teoh, Poh Lin; Wee, Wei Soon (Penerbit Universiti Kebangsaan Malaysia, 2021)
In Malaysia, the circuit breaker is one of the most important and essential safety mechanisms in every building. When electricity enters a house, it goes to a circuit breaker box to be divided into a number of circuits. Each of these circuits is protected by a breaker or a fuse. For safety purposes, electrical appliances are designed to keep the current flow at a low level. However, whenever the current flow jumps above the safety level, the circuit breaker does its job by cutting off the circuit. This is done by the conductor’s bending (a bimetallic strip or rod) in the circuit breaker when the wire temperature rises. If the conductor needs to bend upward when heated, the thermal conductivity of the lower metal rod must be higher than that of the upper rod. This paper focuses on the temperature distribution in the conductor of a crude circuit breaker in a fire alarm system by using different materials such as a bimetallic rod. The paper also describes how different materials can affect the efficiency of the fire alarm system. An implicit method makes it possible to tackle such problems. This can be achieved by the development of a simultaneous linear equations’ system for temperature at a specified point in time for the entire interior nodes. Based on the simulation results, it was found that the explicit method (em) is a simple mechanism to solve parabolic partial differential equations (pde). The results can also be improved by using the implicit method to minimize errors.